Posouzení ekonomické efektivnosti výroby elektrické energie z odpadního tepla - Pavelková, Eva; Živělová, Iva (International Society for Science and Engineering, o.s., 2011)
Cílem příspěvku je posouzení ekonomické efektivnosti výroby elektrické energie z odpadního tepla vznikající v průmyslových provozech za využití technologie ORC. Nejprve je vysvětlen princip takovéto výroby, dále je hodnocena její ekonomická efektivnost prostřednictvím výpočtu čisté současné hodnoty, finanční míry výnosnosti a doby návratnosti aplikované na konkrétním případě investičního projektu.

The aim of the paper is to evaluate the economic effectiveness of production of electric power from waste heat created in industrial operations with the use of ORC technology. First, the principles of such production are explained followed by its economic effectiveness assessment by means of calculating the net present value, financial rate of return and payback period of a specific investment project.
Evaluating Economic Effectiveness of Production of Electric Power from Waste Heat